A Base Camp for Scaling AI - Burges, Chris J.C.; Hart, Ted; Yang, Zi; Cucerzan, Silviu; White, Ryen W.; Pastusiak, Andrzej; Lewis, Julia (NASA ADS, 2016)
Modern statistical machine learning (SML) methods share a major limitation with the early approaches to AI: there is no scalable way to adapt them to new domains. Human learning solves this in part by leveraging a rich, shared, updateable world model. Such scalability requires modularity: updating part of the world model should not impact unrelated parts. We have argued that such modularity will require both ``correctability'' (so that errors can be corrected without introducing new errors) and ``interpretability'' (so that we can understand what components need correcting). To achieve this, one could attempt to adapt state of the art SML systems to be interpretable and correctable; or one could see how far the simplest possible interpretable, correctable learning methods can take us, and try to control the limitations of SML methods by applying them only where needed. Here we focus on the latter approach and we investigate two main ideas: ``Teacher Assisted Learning'', which leverages crowd sourcing to learn language; and ``Factored Dialog Learning'', which factors the process of application development into roles where the language competencies needed are isolated, enabling non-experts to quickly create new applications. We test these ideas in an ``Automated Personal Assistant'' (APA) setting, with two scenarios: that of detecting user intent from a user-APA dialog; and that of creating a class of event reminder applications, where a non-expert ``teacher'' can then create specific apps. For the intent detection task, we use a dataset of a thousand labeled utterances from user dialogs with Cortana, and we show that our approach matches state of the art SML methods, but in addition provides full transparency: the whole (editable) model can be summarized on one human-readable page. For the reminder app task, we ran small user studies to verify the efficacy of the approach.